Pengaruh Pemanfaatan Sistem Informasi Akuntansi dan Teknologi Informasi terhadap Kinerja UMKM di Kecamatan Medan Marelan - Julia Austen Sarotani Zebua; Deliyanti Simbolon; Yonson Pane; Inggrit Larasati Br Panggabean (Politeknik Ganesha Medan, 2026)
This study aims to analyze the effect of accounting information systems (AIS) and information technology (IT) utilization on the performance of Micro, Small, and Medium Enterprises (MSMEs) in Medan Marelan District. The research background highlights issues of low productivity, limited access to financing, and the dominance of manual financial recording among MSMEs, which often results in inaccurate reports and weak performance evaluation. AIS emerges as a strategic solution to improve transparency, accuracy, and operational efficiency, while IT supports automation, data security, and faster access to information for decision-making. A quantitative approach with multiple linear regression analysis was employed. The sample was determined using purposive sampling, consisting of 155 culinary MSMEs that had implemented AIS or IT. Validity and reliability tests confirmed that the research instrument was appropriate. Regression analysis revealed that AIS has a positive and significant effect on MSME performance, with a regression coefficient of 0.352, while IT also shows a positive and significant effect with a coefficient of 0.142. The simultaneous F-test indicated that both variables jointly influence MSME performance, contributing 48.6%, while the remaining 51.4% is explained by other factors not examined in this study. These findings emphasize the importance of AIS in enhancing financial reporting and IT in supporting productivity. The study provides practical implications for MSMEs, government, and educational institutions to strengthen digital literacy, technical assistance, and cross-sector collaboration in improving MSME competitiveness in the digital era.